Livio Odescalchi, nipote di papa Innocenzo XI Interessi famigliari e strategie di ascesa nella stagione dell'antinepotismo - Fiorentini, Roberto (Online-Schriften des DHI Rom. Neue Reihe | Pubblicazioni online del DHI Roma. Nuova serie, 2022)
Livio Odescalchi (1652-1713), nephew of Innocent XI, paid the price in his youth for the pope's anti-nepotism policy, who chose to deny him any official position. During the same period, Livio had to submit to the oppressive control of his uncle, his testamentary guardian - an unhappy situation that, at the time, caused him to be considered a symbol of misfortune. In spite of this, the young man was able to lay the foundations for a strategy of economic and social ascent that would later bear fruit. After the death of Innocent XI, a period of compensation began, built on the accumulation of honours and possessions, financial investments, commissions and art trades, patronage, social celebrations, and international networks. This book, based on Roberto Fiorentini's doctoral thesis (Aprilia 1987 - Washington 2019), examines both phases of Livio Odescalchi's life, analysing them in the light of a considerable quantity of archival documents, some of which are completely unpublished.